Multi-Objective Optimization of Acoustical Properties of PU-Bamboo-Chips Foam Composites - JIANG, Yang; CHEN, Shuming; WANG, Dengfeng; CHEN, Jing (Archives of Acoustics, 2017)
In this study, an effective optimization approach was proposed to improve acoustical behaviors of PU foams. The important parameters of PU foams: content of water, silicone oil and catalyst A1 were chosen and their effects on sound absorption coefficient and transmission loss of PU foams were studied by using Taguchi methods. In addition, bamboo chips were incorporated into PU foams as fillers to improve the acoustical properties of PU foams. Four controlled factors: the content of water, silicone oil, catalyst A1 and bamboo chips with three levels for each factor were chosen and Taguchi method based on orthogonal array L9(34) was employed to conduct the experiments. Based on the results of Taguchi’s orthogonal array L9(34), signal-to noise (S/N) analysis was used and developed to determine an optimal formulation of PU-bamboo-chips foam composites.